PENGEMBANGAN MEDIA PEMBELAJARAN (PCGM) PAPERCRAFT GAME MINECRAFT PADA MATERI KEGIATAN EKONOMI UNTUK SISWA KELAS 4 DI SDN TIRON 4 - Asih Nanda Sari; Dhian Dwi Nur Wenda; Erwin Putera Permana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and evaluate the effectiveness of a game-based learning media (Paper Craft Game Minecraft or PCGM) in enhancing students' interest and understanding of economic activities. This learning media is specifically designed for fourth-grade students at SDN Tiron 4, utilizing a more interactive and engaging approach to optimize the learning experience. The research method employed is Research and Development (R&D) using the ADDIE model, which consists of five main stages: needs analysis, design, development, implementation, and evaluation. Research instruments, including questionnaires and interviews, were used to assess the quality of the learning media based on validity, practicality, and effectiveness aspects. The results indicate that Paper Craft Game Minecraft received a validity score of 82% from subject matter experts and media experts, signifying that this media is highly suitable for use in learning. In terms of practicality, it obtained a score of 98%, reflecting ease of use and alignment with the needs of students and teachers. Meanwhile, in terms of effectiveness, the media achieved an excellent score of 92%, indicating its success in improving students' understanding of economic concepts. Based on these findings, it can be concluded that this game-based learning media is effective in enhancing students' comprehension and can serve as an innovative alternative in elementary school learning. The implications of this study highlight the importance of using interactive learning media to create a more engaging learning experience, as well as the need for further development to expand the variety and scope of the material covered.